DETERMINING IMPULSE BUYING BEHAVIOR: AN EMPIRICAL STUDY ON THE MILLENNIAL GENERATION OF SHOPEE PAYLATER USERS - Noni Amalia Ningrum; Edwin Zusrony; Tantik Sumarlin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
New consumption patterns driven by spending habits, particularly from the millennial population, have come with the introduction of new digital financial services such as Shopee PayLater. This study looks at the influence of lifestyle, financial literacy, and the impulsive buying behavior of Shopee Pay Later users in the Semarang Regency. This is a quantitative study which employs the survey method with a Likert scale from 1 to 5. The respondents of the survey were 60 millennials aged 28-35 years who used Shopee PayLater at least once over the last 6 months. The respondent data were processed using the SmartPLS 4.0 software and analyzed with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. Both lifestyle and financial literacy are found to have a positive and significant influence, both partial and simultaneous, on impulse buying behavior. This denotes that financial illiteracy and a consumptive lifestyle have the propensity to induce impulse buying behavior, in the absence of control mechanisms. This research serves as a practical basis for initiating discourse on policy frameworks within the fields of education and social finance aimed at less financially savvy millennials in the digital globalized world.